IMPLEMENTASI KEBIJAKAN PENANGGULANGAN KEMISKINAN DI KOTA PALU - Marliya, Marliya (Katalogis, 2013)
This research started from the phenomenon of poverty eradication policies in Palu, The Research problem of this research was how the process of implementation of poverty eradication policies in Palu. The theory used to study the poverty eradication policy was the theory of policy by edward III to aspects studied were communication bureaucratic, structure, resources, and disposition. This research was qualitative design, the method of data collection was done by using in-depth interview, observation and documentation, informants selected were policy makers, implemeneters, and beneficiaries. Data analysis was performed through data collection data reduction, and the technique of triangulation data. The results of research showed the communication aspect of the theory advanced by edward III on poverty eradication in palu has not been going well, while the resource aspect of the policies implementation based on the results of research has not shown good results, lack of experience of policies implementers, especially the aid companion program to the poor society and not transparent to the aid provided.